Juridical Review of the Right to Royalty Payments For Songwriters Based on Law Number 28 Of 2014 Concerning Copyright (Case Study of Ari Bias Vs Agnes Monica) - Oktavianto Setyo Nugroho (Fox Justi : Jurnal Ilmu Hukum, 2025)
Royalty payments for songwriters are very important to protect economic rights and maintain the ecosystem of the Indonesian Music Industry. But in its implementation, payment of song royalties is often ignored by Singers and Event Organizers. For example, in the case of copyright infringement experienced by Ari Bias who claimed to have never received royalty payments for the use of the song “Bilang Saja” sung by Agnes Monica for 20 years. This case reflects the weak legal protection of the economic rights of songwriters in Indonesia, especially in the distribution of royalties from Performers and National Collective Management Institutions (LMKN). This research uses a normative juridical method with a statutory approach and literature study, and uses secondary data as material for analysis. The results showed that although Law Number 28 of 2014 concerning Copyright has clearly regulated the payment of royalties to songwriters, its implementation has not been running optimally. Lack of awareness from Singers and Concert Organizers, not allocated budget for Performers to pay royalties to Songwriters and weak law enforcement are the main challenges. It is necessary to strengthen the royalty distribution mechanism, the active role of the state and the awareness of the Performers in guaranteeing the economic rights of Songwriters. This study is expected to contribute to the renewal of the copyright protection system in Indonesia.